Optimum Barrier Height for SiC Schottky Barrier Diode. (31st July 2013) - Hafez, Alaa El-Din Sayed; Abd El-Latif, Mohamed
Abstract : The study of barrier height control and optimization for Schottky barrier diode (SBD) from its physical parameters have been introduced using particle swarm optimization (PSO) algorithm. SBD is the rectifying barrier for electrical conduction across the metal semiconductor (MS) junction and, therefore, is of vital importance to the successful operation of any semiconductor device. 4H-SiC is used as a semiconductor material for its good electrical characteristics with high-power semiconductor devices applications. Six physical parameters are considered during the optimization process, that is, device metal, mobile charge density, fixed oxide charge density, interface trapped charge density, oxide thickness, and voltage drop across the metal-semiconductor contact. The optimization process was performed using a MATLAB program. The results show that the SBD barrier height has been optimized to achieve a maximum or minimum barrier height across the contact, in addition to the ability of controlling the physical parameters to adjust the device barrier height.